ANALYSIS OF CARBON STOCK AND SEQUESTRATION POTENTIAL IN AGROFORESTRY PROTECTION FORESTS OF PINE AND COFFEE AND ITS IMPLICATIONS FOR CLIMATE CHANGE MITIGATION (CASE STUDY: BANJARAN RPH) - Husna, Izzatul
Indonesia has vast forest areas, with 29.6 million hectares of forests being protection forests. Protection forests have the potential for carbon sequestration, which is the capture and longterm storage of carbon from the atmosphere. The ability of protection forests to perform carbon sequestration is one form of climate change mitigation strategy that can have monetary valuation. This study aims to determine the potential carbon stock reserves and their monetary valuation as an effort to enhance forest conservation. Plot 32A, which consists of agroforestry with Pinus merkusii and Coffea arabica, was chosen as a comparison to forests with other dominant pine species. The method used to measure carbon stock is non-destructive, following the SNI 7724:2011 standard and the allometric equations from previous studies. The carbon reserves in plot 32A range around 2,554.449 tons of carbon or 89.32 tons of carbon per hectare, with the estimated end of productive period between the years 2043 and 2053 and a maximum carbon absorption rate of 17.07 tons of carbon per year. With a moderate biodiversity index, low evenness, and moderate dominance, plot 32A has an economic valuation of Rp24,499,787.18 per hectare, in accordance with the applicable REDD+ scheme.